2020
DOI: 10.3102/0162373720973727
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Developmental Math on STEM Participation in Community College: Variation by Race, Gender, Achievement, and Aspiration

Abstract: We use regression discontinuity design to examine the impact of placing into developmental math on science, technology, engineering, and mathematics (STEM) participation in community colleges and whether these relationships differ for underrepresented racially minoritized (URM), women, STEM-oriented, and STEM-aspiring students. Results show that lower math placement was a deterrent to both math progression and STEM participation, especially for those at the margin of placement in transfer-level math. Subgroup … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 65 publications
0
5
0
Order By: Relevance
“…Especially regarding gender, several studies have reported that not only do more women than men attend university, but more women than men are likely to graduate (Dayioğlu & Türüt-Aşik, 2007;Hyde & Kling, 2001;McDaniel, 2012). Gender and racial identity are also important factors to consider in understanding the relationship between developmental education and academic momentum (Park & Ngo, 2021). Due to the vast cultural differences between Iraq and the United States with respect to gender and ethnic identity, these two constructs received particular attention in this study.…”
Section: Student Demographicsmentioning
confidence: 98%
See 2 more Smart Citations
“…Especially regarding gender, several studies have reported that not only do more women than men attend university, but more women than men are likely to graduate (Dayioğlu & Türüt-Aşik, 2007;Hyde & Kling, 2001;McDaniel, 2012). Gender and racial identity are also important factors to consider in understanding the relationship between developmental education and academic momentum (Park & Ngo, 2021). Due to the vast cultural differences between Iraq and the United States with respect to gender and ethnic identity, these two constructs received particular attention in this study.…”
Section: Student Demographicsmentioning
confidence: 98%
“…Because one of the challenges of providing developmental education in undergraduate coursework is students' frustration with the amount of time they must spend in developmental courses, which are not credited toward their respective degrees (Eberly, 2018;Park & Ngo, 2021;Rutschow & Schneider, 2011), some scholars have argued for accelerating developmental education sequences to increase students' academic momentum (e.g., Daugherty et al, 2019;Hodara & Smith Jaggars, 2014). Schudde and Keisler (2019) and Boatman (2021), for example, both found a strong relationship between participating in accelerated developmental education and key indicators of academic momentum, including completing college-level math courses and total credit accumulation.…”
Section: Academic Momentummentioning
confidence: 99%
See 1 more Smart Citation
“…This problem is evident in the attrition rate of students from science, technology, engineering and mathematics majors. Despite growing demand by U.S employers and financial incentives by the private and public sectors to increase STEM degree production, the number of STEM graduates from U.S. postsecondary institutions continues to fall short of market demand (E. S. Park & Ngo, 2021). There is evidence to suggest students' early course load and progress strongly impact academic momentum (Adelman, 2006;Wang, 2015).…”
Section: The Pitfalls Of Developmental Mathematicsmentioning
confidence: 99%
“…It is not enough for faculty to teach mathematical rules and methods to create a foundation for the mastery of mathematical operations (Tularam, 2018). The literature acknowledges the problems postsecondary education has faced with the traditional teacher-led approach to developmental education (Jaggars et al, 2015;E. S. Park & Ngo, 2021;Rutschow & Mayer, 2018).…”
Section: Major Finding 1: Students' Role In Managing the Learning Exp...mentioning
confidence: 99%